Need Analysis of Islamic-Based English Reading Materials for Junior High School Students in Pesantren - Kusumah P., R. Medina; Imani, Anugrah (Journal of English Education and Teacher Trainer, 2025)
he purpose of this study is to analyze the need for English reading materials that integrate Islamic values and teachings for first-year students of junior high school at Kulliyatul Muaalimin Islamiyah (KMI) Pesantren (Islamic School). Many Islamic schools in Indonesia lack resources that meet specific needs and often rely on general English books from the Ministry of Education and Culture or commercial books with no Islamic content materials. This study aims to identify the reading material needs of first-grade students at KMI Darul Azhar in Cianjur, West Java, with a focus on Islamic principles and their relevance to educational content. The research employed interviews with the headmaster and with first-grade English teachers. The questionnaire to the students also was utilized, to identify their insights regarding the current curriculum, desired learning outcomes, and the importance of incorporating Islamic values within the English language program. The results of the questionnaire indicate that 77.3% of students expressed their need for Islamic English reading materials for the first grade of KMI. Moreover, based on the interview results gained from the headmaster and two English teachers, the findings indicate that there is a need to incorporate Islamic values into learning materials and curriculum, including: 1) learning motivation, which consists of stories (hikayat) about ethics, character (akhlak), cleanliness, and tawhid; 2) integration of the pillars of faith and Islam; 3) lessons on Islamic practices through daily activities and storytelling. Specifically, the findings show that the Islamic values that are the most needed by Pesantren, with the result of 81.8% were 4) adab (proper behavior) and akhlak. Additionally, students prefer reading materials that include images or illustrations. This helps students build a foundation for understanding Islamic principles and values, expand their vocabulary, and improve their English skills. By identifying these needs, the study seeks to contribute to the development of age-appropriate and culturally relevant English reading materials that promote both Islamic knowledge and English language proficiency. Researchers and teachers can enhance learning experiences for their students by integrating these Islamic principles directly into the curriculum and adapting reading materials to align with Islamic teachings, tailored for the first grade at junior high school levels in KMI Pesantren.